The purine derivative PI-55 blocks cytokinin action via receptor inhibition - Spíchal, Lukás; Werner, Tomás; Popa, Igor; Riefler, Michael; Schmülling, Thomas; Strnad, Miroslav (The FEBS journal, 2009)
One of several potential approaches to study mechanisms of action of biologically active compounds is to develop their agonists and antagonists. In the present study, we report the identification of the first known molecule antagonizing the activity of the plant hormone cytokinin at the receptor level. This compound, 6-(2-hydroxy-3-methylbenzylamino)purine, designated PI-55 in the present study, is structurally closely related to cytokinin 6-benzylaminopurine, but substitutions at specific positions of the aromatic side chain strongly diminished its cytokinin activity and conferred antagonistic properties. PI-55 competitively inhibited the binding of the natural ligand trans-zeatin to the Arabidopsis cytokinin receptors cytokinin response 1 (CRE1)/Arabidopsis histidine kinase (AHK) 4 and AHK3 and repressed induction of the cytokinin response gene ARR5:GUS. Genetic analysis revealed that CRE1/AHK4 is the primary target of PI-55. Cytokinin bioassays also demonstrated the anticytokinin effect of PI-55 in several other species. Furthermore, we show that PI-55 accelerated the germination of Arabidopsis seeds and promoted the root growth and formation of lateral roots, thus phenocopying the known consequences of a lowered cytokinin status and demonstrating its potential to inhibit cytokinin perception in planta. PI-55 is the first example for the targeted development of a cytokinin antagonist and represents an initial step for the preparation of cytokinin antagonists with broad activity and reduced agonistic properties.
Keywords: kinetika; proteinkinasy; cytokininy; Adenine; Cytokinins; signální transdukce; Receptors, Cell Surface; reportérové geny; Signal Transduction; Arabidopsis Proteins; adenin; regulátory růstu rostlin; semenáček; Plant Roots; proteiny huseníčku; rostlinné proteiny; kořeny rostlin; Genes, Reporter; kompetitivní vazba; Escherichia coli; Seedlings; Protein Kinases; Plant Proteins; Binding, Competitive; Kinetics; Purines; puriny; receptory buněčného povrchu; Plant Growth Regulators; Arabidopsis